Professional Career Choice: Predictive Model in Students of a Private University in Arequipa (Peru) - Franco Delgado, Elva (2023)
The present investigation aimed to design and validate a predictive model that includes variables of the individual, the variables of the context and of academic experience and the expectations of results in the choice of the professional career in students of a private university of Arequipa. This is an empirical study, with associative strategy and transversal predictive design, whose population was made up of a total of 2,228 incoming students of the academic period 2022-I, whose data collection technique was the survey and the instrument the questionnaire. Among the results, it was found that gender and age are predictors of the choice of university career, so as academic experience, favorite subject indicator and the outcome expectations.